THE ROLE OF BRAND IMAGE IN MEDIATING SOCIAL MEDIA MARKETING AND ELECTRONIC WORD OF MOUTH TOWARDS PURCHASE INTENTION ON EMINA PRODUCTS IN PADANG PANJANG CITY - Fazri, Indah Lailatul; Evanita, Susi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the influence of social media marketing, electronic word of mouth (e-WOM), and brand image as mediating variables on purchase intention on Emina products in Padang Panjang City. This type of research is quantitative with a sample of 140 respondents who know Emina through social media but have never purchased the product. Data were collected using an online questionnaire and analyzed with SmartPLS. The results showed that social media marketing and brand image significantly positively affect purchase intention. Meanwhile, e-WOM does not have a significant effect on purchase intention. Social media marketing and e-WOM have a significant positive effect on brand image. Brand image is also proven to be a mediating variable that affects the relationship between e-WOM and purchase intention but does not mediate the effect of social media marketing on purchase intention. Keywords: Purchase Intention; Social Media Marketing; Electronic Word of Mouth; Brand Image; Product Emina